Analisis Gelombang Elektromagnetik terhadap Efisiensi Sel Surya Generasi Baru - Dika Ayu Wulandar; Hijrawati Ayu Wardani (Journal of New Trends in Sciences, 2024)
Solar energy is one of the most promising renewable energy sources to support the transition toward clean energy, yet conventional solar cell technology still faces efficiency limitations. Perovskite materials offer a potential solution due to their superior optoelectronic properties, although challenges related to stability and toxicity remain. This study aims to analyze the interaction of electromagnetic waves with perovskite materials and to evaluate the effect of nano-scale anti-reflective coatings on improving energy conversion efficiency. The research employed a combination of electromagnetic simulations using specialized software and laboratory experiments with miniature perovskite solar cell prototypes. Simulation results demonstrated higher electromagnetic field intensity within the active layer after the addition of anti-reflective coatings, with photon absorption increased by 15–18%. Experimental validation revealed that the energy conversion efficiency improved from 16.8–17.5% without anti-reflective layers to 20.5–21.3% with TiO₂- and SiO₂-based coatings. Optical characterization using a spectrophotometer confirmed enhanced light absorption up to 90% at specific wavelengths, while SEM analysis showed that smoother and more uniform SiO₂ coatings contributed to superior performance compared to TiO₂. Minor discrepancies between simulation and experimental results were attributed to fabrication variations, yet both approaches exhibited consistent improvement trends. These findings highlight that integrating perovskite materials with nano-scale anti-reflective coatings is a key strategy for enhancing the efficiency of next-generation solar cells while supporting future clean energy sustainability.